Mucin expression in mucinous pancreatic cysts: Can string sign test predict mucin types? A single center pilot study - Köker, İbrahim Hakkı; KÖKER, İBRAHİM HAKKI; Ünver, Nurcan; MALYA, FATMA ÜMİT; Malya, Fatma Ümit; Uysal, Ömer; BİBERCİ KESKİN, ELMAS; Şentürk, Hakan; Biberci Keskin, Elmas; ŞENTÜRK, HAKAN (My University, 2020)
Background: Mucinous pancreatic cystic lesions (PCLs) express different mucin (MUC) types according to their histomorphologic types. High cystic fluid viscosity may help in the detection of mucinous PCLs. We hypothesized that high cystic fluid viscosity may be suggestive of a certain MUC type in mucinous PCLs. Methods: Prespecified MUC types (MUC1, MUC2, MUC4, MUC5AC, and MUC6) were evaluated in 18 definitively diagnosed mucinous PCLs with sufficient tissue material and prediagnostic cyst fluid viscosity evaluation—string sign (SS)—test. We evaluated the agreement of MUC expression with positive SS test results. Later, we compared cystic fluid carcinoembryonic antigen (CEA) between the prespecified MUC expressing and nonexpressing cyst types. Results: A total of 18 mucinous PCL patients, 11 females, with mean age ± SD (59.7 ± 13.3) were included. Almost all malignant mucinous PCLs expressed MUC1 (71.4%) (P = .023). We found no significant agreement between the prespecified MUC types and positive SS, except MUC4 which had mild agreement. Also, no significant relation was found between cystic fluid CEA levels and MUC expression (P = .584). Conclusion: We did not detect a significantly moderate or good agreement between the prespecified MUC types and SS test. MUC1 was highly expressed in malignant mucinous cysts; however, it was incompatible with the SS test. MUC4 expression showed mild agreement with the SS test in a small number of patients
Keywords: String sign; Pancreas cyst; MUC; malignancy